Tantangan Akuntansi Dalam Pengungkapan Corporate Sosial Responsibilities dan Pembangunan Berkelanjutan - AKBAR YUSUF (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2015)
The purpose of this study to determine the accounting challenges in the disclosure of corporate socialresponsibilities and sustainable development by using a conceptual study approach. The study shows that thechallenges faced in the field of accounting for sustainable development is the complexity and uncertainty ofthe subject, which began with the absence of a clear definition to be understood about "sustainabledevelopment", the accountant should have an important role to determine the sustainability, theinconvenience of the relationship between sustainability and the main purpose of business, practicaldifficulties are the current accounting system did not facilitate the inclusion of environmental and socialfactors external to the organization's operations. This study suggests the role of accountants to improve thetransparency of business activities, particularly in the areas of social and environmental impacts.